PENGARUH SIKAP, NORMA SUBJEKTIF DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP NIAT UNTUK MENGELUH - Arimbawan, Jefri; Warmika, Gede Ketut (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
The purpose of this study was to determine the influence of attitudes, subjective norms, and perceived behavioral control on the intention to complain to the students of the Faculty of Economics and Business extension Udayana University. This study used a quantitative research by using surveys and questionnaires to 110 respondents. Data analysis techniques used in the study of multiple linear regression analysis. It was found that the variable attitude positive and significant effect on the intention to complain to the students of the Faculty of Economics and Business Extensions Udayana University. Subjective norm variable positive and significant effect on the intention to complain to the students of the Faculty of Economics and Business Extensions Udayana University. Perceived behavioral control variable positive and significant effect on the intention to complain to the students of the Faculty of Economics and Business Extensions Udayana University.
Keywords: Sikap, Norma Subjektif, Perceived Behavioral Control, Niat Mengeluh